Investigating Antibiotic Resistance Pattern and Prevalence of Class I, II, III Integron Genes in K. Pneumoniae Isolated from Clinical Samples in Sahrekord, Iran - Marzeyeh Soleymanian; Elahe Tajbakhsh; Zahra Bam zadeh (Fasa University of Medical Sciences, 2018)
Background & Objective: Acquiring integron is an important factor in multidrug resistance in the intestinal gram negative microorganisms. The most common integron cassette contains the genes associated with resistance to a wide range of antimicrobial agents. The aim of this study was to determine the prevalence of class 1, 2 and 3 integron genes in Klebsiella pneumoniae strains which was isolated from clinical samples in Shahrekord. Material & Methods: In this study antibiotic resistance pattern of 64 strains of Klebsiella pneumonia isolated from clinical samples in medical diagnostic laboratories in Shahrekord were tested by disk diffusion. In order to determine the prevalence of integrons class 1, 2 and 3 were used as specific primers. Results: After performing antibiogram tests, the most resistant was observed to be ampicillin (90.6%) and the lowest resistance one was imipenem (9.3%). Class 1, 2 and 3 integron were observed in 8 isolates (12/5%), 6 isolates (9/4%) and 10 isolates (15/62%). In 40 isolates were not observed Integron genes. In the statistical analysis by Fisher exact test between class 1 integron and resistance to the ampicillin significant association was observed. Conclusion: Resistance genes are located on the integrons and can be transmitted from one strain to another and disseminate resistance in the hospital or other environments, it is important to identify these types of antibiotic resistance genes twofold has done.